Enabling Digital Capabilities with Technologies: A Multiple Case Study of Manufacturing Supply Chains in Disruptive Times - Marco Ardolino; Anna Bino; Maria Pia Ciano; Andrea Bacchetti (Systems)
In the rapidly changing digital economy, manufacturing companies are under growing pressure to adopt new approaches to business management by developing digital capabilities. This research explores the role of digital technologies in enabling these capabilities, using the Digital Capability Model (DCM) as a guiding framework. While previous research often focused on theoretical perspectives, this study operationalizes the DCM by identifying specific applications of digital technologies that enhance business processes. Through a multiple case study methodology, eight manufacturing companies were examined to assess how digital technologies foster the development of digital capabilities. The case studies provide practical insights into the application of these technologies and their impact on organizational resilience and competitiveness, particularly in response to global disruptions such as the COVID-19 pandemic. Our findings reveal that certain technologies are more promising than others for enhancing digital capabilities and that their strategic implementation significantly improves a company’s ability to navigate uncertainty. Embracing digital transformation not only mitigates operational risks but also ensures sustainable competitive advantages in an increasingly volatile and complex environment. This research bridges the gap between theory and practice, offering actionable insights for managers to strategically develop and leverage digital capabilities for long-term success.